Building Qur'an Involvement in TPQ Miftahul Jannah: Analysis of Pedagogical Education Factors, Environment and Students' Self-Regulation - Rahmawati, Desy (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the role of pedagogy, social environment, and self-regulation in building engagement in learning the Quran at TPQ Miftahul Jannah. The study used a descriptive qualitative approach with observation, interview, and documentation techniques. The results showed that the application of the Qiro'aty method, the creation of a religious and enjoyable learning atmosphere, and positive social interactions between teachers and students were able to increase student engagement in learning. However, student self-regulation still needs to be strengthened through ongoing mentoring. This study confirms that the synergy between effective pedagogy, a conducive environment, and strengthening self-regulation is the key to engagement in learning the Quran.